Pendekatan Rasio Fibonacci Dan Fuzzy Logic Sebagai Analisis Teknikal Dalam Menentukan Keputusan Investasi Saham: Fibonacci Ratio Approach And Fuzzy Logic As Technical Analysis In Determining Stock Investment Decisions - Meiliza, Dewi Ratiwi; Prasojo, Bayu Hari (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2019)
One form of approach used to analyze stock prices is by applying Fibonacci ratios and Fuzzy Logic analysis. The purpose of this study is (1) to apply the Fibonacci ratio approach to determine stock support and resistance levels in food and beverage sub-sector companies on the IDX, (2) to apply fuzzy logic analysis based on support and resistance levels with the Fibonacci ratio approach to sub company the food and beverage sector on the IDX, (3) to provide investment decision recommendations in the form of linguistic information on stock price movements in the food and beverage sub-sector companies on the IDX. The research design used in this study is a case study of the price movements of ten shares in the food and beverage sub-sector companies on the Stock Exchange. Researchers used a research design with secondary data. Furthermore, stock price movement data were analyzed using a merging analysis approach with Fibonacci ratios and fuzzy logic analysis with fuzzy systems so that an investment decision recommen- dation was obtained in the form of linguistic information. Based on the results of the study showed that technical analysis of stock price move- ments using Fibonacci ratios and fuzzy logic analysis can be used properly. Furthermore, the results of this linguistic information can be utilized by investors who do not own shares and who already have shares, but the results of this data analysis are not absolute and must be adjusted to the conditions in their application.